A look at polyploidy and plant breeding - Iannicelli, Jesica; Escandon, Alejandro Salvio (Heighten Science Publications, 2022)
Polyploidization is a process that generates genetic variability and therefore one of the engines of biological evolution. Since polyploidization produces important changes in the phenotype, mainly an increase in the size of the organs (i.e.: flowers and fruits), it is also a very important and powerful tool for plant improvement. Despite its intense use in breeding programs for various species, very little is known so far about the nature of this phenomenon. This work presents a brief review of the results obtained by the use of this tool in plant breeding and also raises some reflections on its mechanism of action.